GitOps and Kubernetes video edition - Yuen, Billy; Yuen, Billy; Matyushentsev, Alexander; Ekenstam, Todd; Suen, Jesse (Manning Publications, 2021)
A really great book for understanding and implementing GitOps! Matthieu Evrin, AddÉnergie Technologies GitOps and Kubernetes introduces a radical idea--managing your infrastructure with the same Git pull requests you use to manage your codebase. In this in-depth tutorial, you'll learn to operate infrastructures based on powerful-but-complex technologies such as Kubernetes with the same Git version control tools most developers use daily. With these GitOps techniques and best practices, you'll accelerate application development without compromising on security, easily roll back infrastructure changes, and seamlessly introduce new team members to your automation process. about the technology With GitOps you use the Git version control system to organize and manage your infrastructure just like any other codebase. It's an excellent model for applications deployed as containers and pods on Kubernetes. about the book GitOps and Kubernetes teaches you how to use Git and the GitOps methodology to manage a Kubernetes cluster. The book interleaves theory with practice, presenting core Ops concepts alongside easy-to-implement techniques so you can put GitOps into action. Learn to develop pipelines that trace changes, roll back mistakes, and audit container deployment. what's inside Managing secrets the GitOps way Controlling access with Git, Kubernetes, and Pipeline Branching, namespaces, and configuration about the audience For developers and operations engineers familiar with continuous delivery, Git, and Kubernetes. about the authors Billy Yuen , Alexander Matyushentsev , Todd Ekenstam , and Jesse Suen are principal engineers at Intuit. They are widely recognized for their work in GitOps for Kubernetes. Vital for understanding what GitOps is, and what tools will get you there. JChris Viner, Forged Development How to deliver operational excellence through industry-level practices. Satej Sahu, Honeywell This book takes two massively complex topics and breaks them down into understandable and approachable tools. Samuel Brown, Expel NARRATED BY JULIE BRIERLEY.